“A very civil idea …”: art history, transculturation and world-making - with and beyond nation - Juneja, Monica (Zeitschrift für Kunstgeschichte, 2018)
Must a global art history follow the logic of economic globalization or does it call for an alternative conception of critical globality to be able to effectively theorize relationships of connectivity that encompass disparities as well as contradictions? This article investigates the potential of transculturation as a method to address a number of the pressing questions faced by art history in the wake of the ‘global turn’. It begins by tracing the genealogies of approaches that sought to incorporate the ‘world’ within the scope of the discipline a century ago and queries the epistemic legacies of this historiographic move. By shifting the focus of enquiry beyond Euro-America, it looks for a way through which the practice of art history can translate the intellectual insights of non-European experiences into globally intelligible analyses.